PELAKSANAAN PERMOHONAN IZIN POLIGAMI DI PENGADILAN AGAMA KLAS IA PADANG - Faura, Rita (UNES Journal of Swara Justisia, 2021)
The existence of a law that regulates polygamy permits is intended to establish public order, provide legal protection and guarantees for the rights and obligations of regulatory relations. In addition, to protect the rights of everyone. So, the formal conditions of polygamy will care to achieve the goal of judicial marriage. Therefore, the permission of polygamy philosophically makes the goal of marriage to be achieved and educates the public to be aware of the regulations.